PENGGUNAAN BAHAN TAFFETA DAN KATUN UNTUK ROK LINGKARAN - Miftahurrahmi, Miftahurrahmi; Zahri, Wildati; Ysnidawati, Yasnidawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
Circle skirt is a skirt made of cloth folded lengthwise with a piece of half-circle. Thenput together on the sides to form circle. The fabric used unruk circle skirt is made of taffetaand cotton materials because both materials are theoretically suitable for the manufacture of acircle skirt. The purpose of this study to describe the use of taffeta and cotton circle skirt.This type of research is a descriptive study with quantitative methods. Variableresearch is the use of taffeta and cotton circle skirt. Methods of data collection usingassessment format sheet with check mark (ïƒ–) and assessed by a panel of 3 expertsdressmaking lecturer in the Department of Kesajahteraan Keluarga. The data analysistechnique used is descriptive statistical techniques with percentage calculations using dataMicrosoft Office Excel 2007.The results showed the use of taffeta to have a circle skirt suits their fitting (fit) is veryflat located in the abdomen on the front and flat on the buttocks. Balance circumferencebelow average on the side skirts and the same length between the front and rear. Waves thatfall parallel to the diagonal direction. Average wave fall in the middle of the front, sides andbetween the side and center front. Has a larger wave than cotton. As well as the A-linesilhouette and suitable for use by all age groups in women skinny for festive occasions. Theuse of cotton to have a circle skirt suits their fitting (fit) is very flat from the abdomen andvery flat in the ass on the back. Balance under the circumference of a circle skirt hangs veryflat on both sides of the legs and the same length at the front and rear. The fall of the wavesare not too straight parallel to the diagonal direction. Wave skirt very average fall in themiddle of the front, sides and between the side and center front. The magnitude of the wave isnot as big waves generated taffeta material so as to make a circle skirt H-line silhouette. andsuitable for use by all age groups in the fat woman for everyday wear, travel and relax.Kata kunci: Penggunaan Bahan Taffeta Dan Katun Untuk Rok lingkaran.